ANALISIS PENGARUH PENGELUARAN PEMERINTAH SEKTOR PERLINDUNGAN SOSIAL DAN KESEHATAN TERHADAP KEMISKINAN DI PROVINSI ACEH - Jose Firdaus Sirait; Ferayanti Ferayanti; Meutia Firdaus Qudraty (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2022)
Abstract This study aims to determine the effect of social protection and health variables on poverty in Aceh Province in 2011-2020. The type of research used is descriptive quantitative research with panel data regression method and choose a fixed effect model approach (Fixed Effect). The data used is secondary data, which consists of data on government spending in the fields of social protection, health sourced from the Directorate General of Financial Development (DJPK) and data on the number of poor people sourced from the Provincial Central Statistics Agency (BPS). Aceh Province. The results of this study indicate that government spending in the field of social protection has a positive and significant effect on poverty, while government spending on health has a negative and significant effect on poverty in Aceh Province in 2011-2020. From the results of this research, it is hoped that the government needs to improve the distribution pattern and allocation of social protection funds so that aid and subsidy programs can be more optimal and on target, such as the Family Hope Program (PKH), Pre-Employment Card program, bidikmisi program, and other programs.Keywords: Poverty, Government Spending on Social Protection and Health.